CSR serves to compete in the sport industry? An exploratory research in the football sector in Peru - Quispe Salguero, Julio (2016)
Corporate social responsibility (CSR) is a concept used by firms to obtain competitiveness. Although the focus of academic research has been on identifying the link between financial and social performance, the causal evidence of this relationship remains unclear. Our research attempts to fill this gap by validating hypotheses indicating that the effect of CSR on business competitiveness requires integrating other variables. The literature review shows limited research conducted on CSR and professional sports in emerging countries. Our article fills these gaps by investigating the effect of CSR on competitiveness of football teams. Our results will expand the applicability of CSR to other organizations, while at the same time offering recommendations to a sector with economic and sociological global repercussions.